Social Service Advisory to a Tutorial Council in the southern region of Brazil: an experience report (Research, Society and Development, 2020)
The work aims to present the experience report from the Extension Project: "Social Service and Guardianship Council: Necessary mediations for the integral protection of children and adolescents" registered in the SIPPEE Platform (registration 08.021.18) linked to the Federal University of Pampa, campus São Borja (RS) in 2017/2018. As a methodology, the qualitative explanatory approach was chosen and for the analysis of reality, the dialectical-critical method and its core categories were used: historicity, totality, contradiction and mediation; it developed as an experience report. Among the results it was pointed out: the low scientific production regarding the theme; the still timid insertion of Social Work professionals in these socio-occupational spaces; the presence of difficulties for professional practice, such as the loss of the institution's historical records, “Minutes of the Tutelary Council (CT)”; lack of documented information regarding the resources available in the municipality; the fragility of administrative flows in meeting demands; the absence of systematization of CT data. Thus, it was concluded that Assistance to the CT is fertile ground for professional intervention investigation; contribution to support, the construction of different strategies to strengthen the TC; the need for professional Social Assistants Advisors in the TC (s) in order to expand and consolidate the discussion regarding the Doctrine of Integral Protection to children and adolescents.